Study comparing the clinical profile of patients with stroke in diabetic and non-diabetic patients - Kumar, G. Sathish; Rajeswaran, S.; Padmanaban, U. B. (International Journal of Advances in Medicine, 2019)
Background: A stroke occurs when a blood vessel that carries oxygen and nutrients to the brain is either blocked by a clot or bursts (or ruptures). Computed tomography (CT) and magnetic resonance imaging (MRI) was done to determine the type of stroke. Diabetes mellitus is a well-recognized risk factor for ischemic stroke. The study was undertaken to assess the clinical characteristics, outcome pattern and to compare the pattern of stroke in diabetics and non-diabetics. Methods: An observational cross-sectional prospective study wherein a hundred stroke patients being admitted to MGMGH, Trichy were sampled and the clinical profile along with outcome is compared in diabetic and non- diabetic populations and the statistical significance of the same. Results: The proportion of patients with poor outcome following stroke was significantly higher in diabetics compared with non-diabetic patients being chi square value was 37.6514 and p value was found to be significantly less than 0.0001. Conclusions: The study resulted the large hemorrhages are twice as much common in the diabetic population compared to the non-diabetic population , the incidence increases with the chronicity of diabetes and the outcome is superior in the non-diabetics compared to the diabetics admitted in Mahatma Gandhi Memorial Government Hospital, Tiruchirappalli, Tamil Nadu, India.